La actuación española en las operaciones de paz. La relación ONG-Fuerzas Armadas: puntos de tensión y de fricción. El caso de los Balcanes - Durán Cenit, Marién; De Cueto Nogueras, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
The aim of this article is to discuss about the governance of the international security and also, about the operational struggles between the NGOs and the Armed Forces. On this sense, we will focus on the analysis of the Spanish action, taking the Balkans as study scenario because it has constituted a breaking point when bringing together different actors as NGOs, civil society and the State’s participation through the Armed Forces, dealing with an unfavourable reaction from the humanitarian community.